(untitled) - Chess, Barry (New York, 2012)
This lab uses real-life case studies as the basis for exercises in the laboratory. This is the only microbiology lab manual focusing on this means of instruction, an approach particularly applicable to the microbiology laboratory. The author has carefully organized the exercises so that students develop a solid intellectual base beginning with a particular technique, moving through the case study, and finally applying new knowledge to unique situations beyond the case study.
Keywords: Microbiology,Vi trùng học